The school heads' strategy for planning to boost the standard of education - Aisyah Fitrisari; Edi Harapan; Achmad Wahidy (Indonesian Institute for Counseling, Education and Therapy (IICET), 2021)
The main objective of the analysis was to evaluate the Strategy of the Principal in Preparing to Enhance the Standard of Education at MTs Negeri 1 Musi Banyuasin. In carrying out the vision and mission and obligations, namely through the enhancement of religious values of students and programs of teacher competence. Qualitative analysis is the research used. Via evaluation, interviews and reporting, data collection was carried out. Data analysis methods have resulted in data reduction, data presentation and conclusions being drawn. The findings of this study suggest that an improvement in religious values by increasing the completeness of facilities and amenities is the principal strategy in preparing to enhance the standard of education To promote a special space for the Tahfidz AlQuran students for the learning process and to build teacher competencies through a Memorandum of Understanding. Improve teacher competence, teacher success and teaching and learning quality for student performance. In education and training, teachers are assigned to participate, If it is done by the school itself or by the assistance of other educational institutions.